Ivabradine Reduces Chemokine-Induced CD4-Positive Lymphocyte Migration. (5th December 2010) - Walcher, Thomas; Bernhardt, Peter; Vasic, Dusica; Bach, Helga; Durst, Renate; Rottbauer, Wolfgang; Walcher, Daniel
Abstract : Aims. Migration of CD4-positive lymphocytes into the vessel wall is a critical step in atherogenesis. Recent data suggest that ivabradine, a selective I(f)-channel blocker, reduces atherosclerotic plaque formation in apolipoprotein E-deficient mice, hitherto nothing is known about the mechanism by which ivabradine modulates plaque formation. Therefore, the present study investigated whether ivabradine regulates chemokine-induced migration of lymphocytes. Methods and results. Stimulation of CD4-positive lymphocytes with SDF-1 leads to a 2.0 ± 0.1 fold increase in cell migration (P < . 01 ; n = 7 ). Pretreatment of cells with ivabradine reduces this effect to a maximal 1.2 ± 0.1 fold induction at 0.1 µmol/L ivabradine (P < . 01 compared to SDF-1-treated cells, n = 7 ). The effect of ivabradine on CD4-positive lymphocyte migration was mediated through an early inhibition of chemokine-induced PI-3 kinase activity as determined by PI-3 kinase activity assays. Downstream, ivabradine inhibits activation of the small GTPase Rac and phosphorylation of the Myosin Light Chain (MLC). Moreover, ivabradine treatment reduces f-actin formation as well as ICAM3 translocation to the uropod of the cell, thus interfering with two important steps in T cell migration. Conclusion. Ivabradine inhibits chemokine-induced migration of CD4-positive lymphocytes. Given the crucial importance of chemokine-induced T-cell migration in early atherogenesis, ivabradine may be a promising tool to modulate this effect.